Prof. Zbigniew Witold Engel - Doctor Honoris Causa of the Cracow University of Technology - KOSAŁA, Krzysztof (Archives of Acoustics, 2006)
On June 28th 2006 the Rector of the Cracow University of Technology presented the honorary title of Doctor Honoris Causa conferred to Professor Zbigniew Engel by the resolution of the Senate of the University of Technology. The Ceremonial Session of the Senate took place in the Collegium Maius Aula of the Jagiellonian University.Professor Zbigniew Witold Engel, Doctor Honoris Causa of AGH University of Science and Technology, was born on April 1, 1933 in Zawady near Żółkwia, Lvov Voivodship. Between 1950-1955 he studied at the Department of Communication (Mechanics) at the Polytechnic Departments which was a part of the University of Mining and Metallurgy and he obtained the Master of Engineering Title and Diploma of the Master and Engineering.In 1962 he successfully completed his PhD at the Faculty of Mechanization of the Mining and Metallurgy and he obtained the degree of Doctor of Science. In 1973 he obtained the postdoctoral qualifications (the Doctor Habilitatus degree). In 1973 he received the title of an Associate Professor and in 1978 he was granted the degree of a Full Professor.Professor Zbigniew W. Engel occupied a position of the Director of the Mechanics and Vibroacoustics Institute for several years and he made a remarkable contribution in developing this institute. As an expert in the field of applied mechanics and vibroacoustics and also the creator of a vibroacoustics as a new area of science which has gained since worldwide attention - he also held the office of the Head of Chair of Mechanics and Vibroacoustics.Professor Zbigniew Engel's research activity focuses on many topics in the field of mechanics and vibroacoustics particularly in the field of vibroacoustic synthesis of machines and devices, dynamics of machines, linear and nonlinear vibrations of mechanic systems, vibrations in technology, noise in environment, assessment and control of vibroacoustic hazards, the bases of active method of the vibroacoustic hazards suppression, the methods of research into vibroacoustic processes and the Reciprocity and Inversion Principles in vibroacoustics.Professor Zbigniew Engel is the creator of the scientific grounds for a new science - vibroacoustics. He formulated its scope and fundamental objectives that are: the identification of the vibroacoustic energy sources, the identification of vibroacoustic energy transmission and its transformation, the vibroacoustic synthesis of machines and devices, the vibroacoustic diagnostic, the practical application of vibroacoustic processes, also in the field of medicine, the methods of research in vibroacoustic processes, the vibroacoustic Reciprocity Principle and also the inversion methods.Printed scientific attainment of Professor Z. Engel consists of 540 contributions including monographs, text-books, scripts, papers published in scientific journals and presentations at the scientific conferences and congresses. Professor Engel is also an author of 15 patents and a wide variety of unpublished works that was carried out to satisfy the needs of industry and economy.The large part of the overall activity of Professor Z. Engel concerns the didactic activity. He supervised 37 completed doctoral theses and he was a reviewer of over 100 of them. He also reviewed over 50 postdoctoral theses (doctor habilitatus). He issued the opinions concerning several professor's degree applications and many of his collaborators have been granted doctor habilitatus degree and have been appointed professors.